2021
DOI: 10.14245/ns.2040814.407
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection Between Lateral Mass and Inferomedial Edge of the C1 Posterior Arch: A Reference Point for C1 Lateral Mass Screw Insertion

Abstract: Objective: To determine the ideal Atlas (C1) lateral mass screw placement and trajectory using the intersection between the lateral mass and inferomedial edge of the posterior arch as an easily identifiable and reproducible medial reference point. Selection of an ideal entry point and trajectory of C1 lateral mass screw insertion can help to minimize neurovascular injuries. While various techniques for screw insertion have been proposed in the past, they all require extensive dissection of the C1 lateral mass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…On the other hand, advocates of conservative management have reported that unstable atlas fractures can be managed by HVI or rigid collars [ 10 , 11 , 23 ]. They argued that HVI or a rigid collar provides traction to align the fractured lateral masses by ligamentotaxis effect and reduces a stress force below C1–2, thereby preventing subluxation and promoting healing [ 11 , 19 , 23 ]. However, it is doubtful whether the damaged TAL of an unstable atlas fracture can facilitate ligamentotaxis and maintain a lateral slippage until complete healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, advocates of conservative management have reported that unstable atlas fractures can be managed by HVI or rigid collars [ 10 , 11 , 23 ]. They argued that HVI or a rigid collar provides traction to align the fractured lateral masses by ligamentotaxis effect and reduces a stress force below C1–2, thereby preventing subluxation and promoting healing [ 11 , 19 , 23 ]. However, it is doubtful whether the damaged TAL of an unstable atlas fracture can facilitate ligamentotaxis and maintain a lateral slippage until complete healing.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,23 They argued that HVI or a rigid collar provides traction to align the fractured lateral masses by ligamentotaxis effect and reduces a stress force below C1-C2, thereby preventing subluxation and promoting healing. 11,19,23 However, it is doubtful whether the damaged TAL of an unstable atlas fracture can facilitate ligamentotaxis and maintain a lateral slippage until complete healing. In common, osseous injuries heal well with immobilization to treat fractured segments.…”
Section: Outcomes Between Patients Who Underwent Surgical Operation A...mentioning
confidence: 99%